Mixed-Up Sex Chromosomes: Identification of Sex Chromosomes in the X1X1X2X2/X1X2Y System of the Legless Lizards of the Genus Lialis (Squamata: Gekkota: Pygopodidae) - Rovatsos, Michail; Johnson Pokorná, Martina; Altmanová, Marie; Kratochvíl, Lukáš (Cytogenetic and genome research, 2016)
Geckos in general show extensive variability in sex determining systems, but only male heterogamety has been demonstrated in the members of their legless family Pygopodidae. In the pioneering study published more than 45 years ago, multiple sex chromosomes of the type X1X1X2X2/X1X2Y were described in Burton's legless lizard (Lialisburtonis) based on conventional cytogenetic techniques. We conducted cytogenetic analyses including comparative genomic hybridization and fluorescence in situ hybridization (FISH) with selected cytogenetic markers in this species and the previously cytogenetically unstudied Papua snake lizard (Lialis jicari) to better understand the nature of these sex chromosomes and their differentiation. Both species possess male heterogamety with an X1X1X2X2/X1X2Y sex chromosome system; however, the Y and one of the X chromosomes are not small chromosomes as previously reported in L. burtonis, but the largest macrochromosomal pair in the karyotype. The Y chromosomes in both species have large heterochromatic blocks with extensive accumulations of GATA and AC microsatellite motifs. FISH with telomeric probe revealed an exclusively terminal position of telomeric sequences in L. jicari (2n = 42 chromosomes in females), but extensive interstitial signals, potentially remnants of chromosomal fusions, in L.burtonis (2n = 34 in females). Our study shows that even largely differentiated and heteromorphic sex chromosomes might be misidentified by conventional cytogenetic analyses and that the application of more sensitive cytogenetic techniques for the identification of sex chromosomes is beneficial even in the classical examples of multiple sex chromosomes.
Keywords: Animals; srovnávací genomová hybridizace; Female; plazi; ženské pohlaví; telomery; Telomere; karyotyp; pohlavní chromozomy; Male; Sex Chromosomes; Karyotype; Microsatellite Repeats; Comparative Genomic Hybridization; hybridizace in situ fluorescenční; zvířata; mužské pohlaví; In Situ Hybridization, Fluorescence; mikrosatelitní repetice; Reptiles